Preferensi Mahasiswa dalam Menggunakan Platform Digital Payment untuk Layanan Tel-U Carwash: Student Preferences in the Use of Digital Payment Platforms for Tel-U Carwash Services - Saragih, Gigano Nehemia Agra; Kotjoprayudi, Raswyshnoe Boing; Fahrudin, Tora (Institut Agama Islam Negeri Kerinci, 2025)
Purpose: This study aims to identify the most suitable digital payment platform for Tel-U Carwash based on students’ preferences and to analyze the factors influencing their platform selection. Design/methodology/approach: This research employs a quantitative approach. Primary data were collected through questionnaires, with a sample size of 100 respondents. The data were analyzed using descriptive statistics and multinomial logistic regression with the assistance of Google Colab. Findings: Bank transfers via QRIS emerged as the most preferred payment platform. Gender was found to have a significant effect on platform choice, while ease of use, security, and transaction speed did not show a significant effect. Research implications: Further exploration of additional factors beyond the indicators examined in this study is necessary to enable service providers to offer payment options that better align with students’ preferences.